Trying to get over : African American directors after blaxploitation, 1977-1986 - Corson, Keith (University of Texas Press, 2016)
From 1972 to 1976, Hollywood made an unprecedented number of films targeted at black audiences. But following this era known as "blaxploitation," the momentum suddenly reversed for black filmmakers, and a large void separates the end of blaxploitation from the black film explosion that followed the arrival of Spike Lee?s She's Gotta Have It in 1986. Illuminating an overlooked era in African American film history, Trying to Get Over is the first in-depth study of black directors working during the decade between 1977 and 1986. Keith Corson provides a fresh definition of blaxploitation, lays out a concrete reason for its end, and explains the major gap in African American representation during the years that followed. He focuses primarily on the work of eight directors?Michael Schultz, Sidney Poitier, Jamaa Fanaka, Fred Williamson, Gilbert Moses, Stan Lathan, Richard Pryor, and Prince?who were the only black directors making commercially distributed films in the decade following the blaxploitation cycle. Using the careers of each director and the twenty-four films they produced during this time to tell a larger story about Hollywood and the shifting dialogue about race, power, and access, Corson shows how these directors are a key part of the continuum of African American cinema and how they have shaped popular culture over the past quarter century.